2000
DOI: 10.1086/312526
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Photoprocessing of Interstellar Dust Mantles as a Source of Polycyclic Aromatic Hydrocarbons and Other Conjugated Molecules

Abstract: By co-depositing a gas mixture of simple carbon- and nitrogen-containing molecules with water on a 10 K surface and exposing it to ultraviolet radiation, we were able to form a residue. This residue was then placed aboard the EURECA satellite behind a magnesium fluoride window and exposed to solar radiation for 4 months before it was returned and analyzed. The resulting residue is believed to simulate the photoprocessing of organic dust mantles in the interstellar medium. Mass spectrometry indicated that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 29 publications
1
39
0
Order By: Relevance
“…The observation of vinylacetylene in the ice potentially yields a formation pathway towards PAHs to which it is known to be a precursor. This is an interesting finding, because PAHs are ubiquitous in space, and they are generally assumed to form in the outflows of AGB stars, in accordance with the experiments of Greenberg et al (2000) that analyze gas chromatographically residues obtained after UV photolysis of ice and ice residu. The present results hint at a (complementary) bottom-up formation mechanism..…”
Section: Astrophysical Implicationssupporting
confidence: 79%
“…The observation of vinylacetylene in the ice potentially yields a formation pathway towards PAHs to which it is known to be a precursor. This is an interesting finding, because PAHs are ubiquitous in space, and they are generally assumed to form in the outflows of AGB stars, in accordance with the experiments of Greenberg et al (2000) that analyze gas chromatographically residues obtained after UV photolysis of ice and ice residu. The present results hint at a (complementary) bottom-up formation mechanism..…”
Section: Astrophysical Implicationssupporting
confidence: 79%
“…7. Considering that PAHs are associated with the cold dust and thus molecular clouds, possible mechanisms for the enhanced PAH abundance are (1) the synthesis of PAHs in molecular clouds (Greenberg et al 2000), or (2) BG shattering and/or swept up into shells by slow shocks with velocities lower than ∼75 km s −1 (Jones et al 1996;Hunter et al 2006). Sandstrom et al (2010) found that the PAH abundance was correlated with cold dust and CO emission, and suggested the possibility of PAH formation in molecular clouds.…”
Section: Enhanced Star-forming Activity In Regions Around the Giant Smentioning
confidence: 99%
“…Taking advantage of the selectivity and sensitivity of L 2 MS toward PAHs, we have investigated this process by characterizing nonvolatile aromatic photo-products in irradiated interstellar ice analogs (37)(38)(39)(40)(41). This work was performed in collaboration with the NASA Ames Research Center Astrochemistry group and researchers at the University of Leiden.…”
Section: Interplanetary Dust Particles (Idps)mentioning
confidence: 99%
“…In an initial study, photolysis products from interstellar ice analogs comprised only of small molecules (no PAHs) were studied. Various ice analog mixtures containing H 2 O, CO, NH 3 , CH 3 OH, CH 4 , and C 2 H 2 were exposed to both UV and solar radiation (41). Using L 2 MS, we detected a complex mixture of PAH photoproducts that contained evidence of alkylation, hydrogenation, and in some cases the addition of nitrogen (i.e., -NH 2 , -CN, or -NC).…”
Section: Interplanetary Dust Particles (Idps)mentioning
confidence: 99%